Covid-19 As A Non-Traditional Threat To Human Security - Nurhasanah, Siti; Napang, Marthen; Rohman, Syaiful (UI Scholars Hub, 2020)
December 2019 marks a change in the perception of security itself because the enemy is invisible in the form of a virus that can endanger human survival. In this article, the author wants to discuss changes in the perception of